Risk of Recurrent Coronary Events in Patients With Familial Hypercholesterolemia; A 10-Years Prospective Study - Arnesen, Kjell-Erik; Phung, Ann Vinh; Randsborg, Karoline; Mork, Irene; Thorvall, Marlene; Langslet, Gisle; Svilaas, Arne; Wium, Cecilie; Ose, Leiv; Retterstøl, Kjetil (Frontiers in Pharmacology, 2021)
Background and Aim: Real world evidence on long term treatment of patients with familial hypercholesterolemia (FH) is important. We studied the effects of intensive lipid lowering medication (LLM) and optimized lifestyle in the study TTTFH–Treat To Target FH. Materials and Methods: Adults with a first known total cholesterol of mean (95% CI) 9.8 mmol/L (9.5, 10.1) were included consecutively in their routine consultation during 2006. Of the patients 86.4% had a pathogenic FH-mutation and the remaining were clinically diagnosed. We included 357 patients and 279 met for follow-up after median 10.0 (min 8.1, max 12.8) years. Results: Mean (95% CI) low density lipoprotein (LDL-C) was reduced from 3.9 (3.8, 4.1) to 3.0 (2.9, 3.2). More men than women used high intensity statin treatment, 85.2 and 60.8%, respectively. Women (n = 129) had higher LDL-C; 3.3 mmol/L (3.0, 3.5), than men; (n = 144) 2.8 mmol/L (2.6, 3.0), p = 0.004. Add-on PCSK9 inhibitors (n = 25) reduced mean LDL-C to 2.0 (1.4, 2.6) mmol/L. At enrollment 57 patients (20.4%) had established atherosclerotic cardiovascular disease (ASCVD), and 46 (80.4%) of them experienced a new event during the study period. Similarly, 222 (79.6%) patients had no detectable ASCVD at enrollment, and 29 of them (13.1%) experienced a first-time event during the study period. Conclusion: A mean LDL-C of 3.0 mmol/L was achievable in FH, treated intensively at a specialized clinic with few users of PCSK9 inhibitors. LDL-C was higher (0.5 mmol/L) in women than in men. In patients with ASCVD at enrollment, most (80.7%) experienced a new ASCVD event in the study period. The FH patients in primary prevention had more moderate CV risk, 13% in ten years.